PENCIPTAAN CITRA POSITIF MADRASAH MELALUI PEMANFAATAN MEDIA SOSIAL DI MTs SYAMSUL HUDA - Muhammad Faishal Danial (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
The purpose of this study is to describe the efforts to create a positive image of madrasas through the use of social media in MTs Syamsul Huda, this study uses a qualitative approach with descriptive analysis type, data collection techniques are carried out by interviews, observations and documentation. Analysis of the data used consists of data reduction, data delivery, and drawing conclusions. Sources of research data were school principals, teachers and TU staff at MTs Syamsul Huda. The results showed the creation of a positive image in MTs Syamsul Huda through the use of social media is quite good.